SUBSTITUSI TEPUNG UBI JALAR UNGU TERHADAP KUE LUMPUR - Resty Syafitri; Yulia Mandasari (Jurnal Pariwisata Bunda, 2021)
This research is motivated by the fact that there is still no purple sweet potato flour produced and marketed in Indonesia. Therefore, it is necessary to experiment with lumpur cakes by adding purple sweet potato flour. Making sweet potato flour will create food diversification. The purpose of this research was to see how the quality of the lumpur cakes with the use of purple sweet potato flour as raw material in terms of taste, color, texture and aroma. The research method used was the experimental method. The data collection techniques were literature studies and questionnaires. This research was assessed by expert panelists, namely the Bunda Tourism Academy lecturers, while the general panelists were the people surrounding the community. The results of this experimental study using organoleptic tests showed that lumpur cake with 50% purple sweet potato substitution had sufficient sweet potato aroma, quite purple color, soft texture, sweet taste, and sufficient purple sweet potato taste. Lumpur cake with a substitution of 70% purple sweet potato had a purple sweet potato aroma, a purple color, a fairly soft texture, a fairly sweet taste,  and a purple sweet potato taste more.